2001
DOI: 10.1002/app.10124
|View full text |Cite
|
Sign up to set email alerts
|

The interaction mechanism between microorganisms and substrate in the biodegradation of polycaprolactone

Abstract: ABSTRACT:The present work concerns the interplay of the degradation mechanism and the nature of the interaction between microorganisms and substrate. The biodegradation of polycaprolactone films by a pure strain of microorganisms isolated from an industrial composting unit for household refuse was studied in minimal medium with the polymer as sole carbon source. In conditions where the polymer surface is colonized and a biofilm is formed (under a low stirring rate), polymer weight loss is limited, whereas tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…It has been reported that esterase and other kinds of lipase can degrade poly(ϵ‐caprolactone) by hydrolysis 17–19. Microbial attack occurs preferentially in the amorphous phase; this leads to chain rearrangement and an increased crystallinity index 20. PCL biodegradation in soil has been reported to be a slow process; it started after 40 days and took more than 200 days to complete 21, 22…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that esterase and other kinds of lipase can degrade poly(ϵ‐caprolactone) by hydrolysis 17–19. Microbial attack occurs preferentially in the amorphous phase; this leads to chain rearrangement and an increased crystallinity index 20. PCL biodegradation in soil has been reported to be a slow process; it started after 40 days and took more than 200 days to complete 21, 22…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Microbial attack occurs preferentially in the amorphous phase; this leads to chain rear-rangement and an increased crystallinity index. 20 PCL biodegradation in soil has been reported to be a slow process; it started after 40 days and took more than 200 days to complete. 21,22 On the other hand, a previous study showed that a regenerated cellulose film decomposed completely in soil into CO 2 and water after 60 days as a result of the random breakdown of bonds of cellulose macromolecules.…”
Section: Biodisintegration Of the Pcl Nanocomposites In Soilmentioning
confidence: 99%
“…They hypothesized that biodegradation of this material may also occur because of enzymatic hydrolysis via a surface degradation mechanism, similar to that, which has been previously reported for polycaprolactone. [12][13][14] The PCL material has a significantly slower biodegradation rate than other biodegradable polymers (BDP) biomaterials, making it suitable for the design of long-term implantable systems such as Capronor, a US FDA approved contraceptive device. 15 The toxicology of PCL has been studied as part of the evaluation of Capronor, it is currently regarded as non-toxic and tissue compatible.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be pointed out that, although the present study focused on Resilon/Epiphany sealing abilities at time 0, several studies have already demonstrated the weakening of Resilon/epiphany seal even after relatively short storage periods due to degradation of adhesive interface [8,30,43,54] and enzymatic degradation of polycaprolactone [10,49,[55][56][57].…”
Section: Discussionmentioning
confidence: 84%